2021
DOI: 10.3390/ijgi10050349
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Historical Maps and LiDAR Data to Identify Man-Made Landforms in Urban Areas

Abstract: In recent years, there has been growing interest in urban geomorphology both for its applications in terms of landscape planning, and its historical, cultural, and scientific interest. Due to recent urban growth, the identification of landforms in cities is difficult, particularly in Mediterranean and central European cities, characterized by more than 1000 years of urban stratification. By comparing and overlapping 19th-century cartography and modern topography from remote sensing data, this research aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…(i) We demonstrated that signals obtained from scanned and georeferenced historical maps or whole map collections have the potential to enrich remote-sensing-based analyses (e.g., [93]) and to extend the observational window of remote-sensing-based change analysis further back in time. We applied our method to the study of long-term urban change, but similar frameworks could be employed for other applications, such as the analysis of long-term forest dynamics or other types of land cover.…”
Section: Discussionmentioning
confidence: 99%
“…(i) We demonstrated that signals obtained from scanned and georeferenced historical maps or whole map collections have the potential to enrich remote-sensing-based analyses (e.g., [93]) and to extend the observational window of remote-sensing-based change analysis further back in time. We applied our method to the study of long-term urban change, but similar frameworks could be employed for other applications, such as the analysis of long-term forest dynamics or other types of land cover.…”
Section: Discussionmentioning
confidence: 99%
“…Archival maps are a reliable source of knowledge about landform changes in historical times 37 40 ). The Prussian Meßtischblätter maps used in this study are characterised by very high detail and accurate topography and are among the best sources of information on the spatial transformations (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial data analyses constitute a particularly note-worthy method for demonstrating changes within urban areas. Historical data and digital models, on the other hand, can be used to indicate the impact of excavation on land relief in the course of anthropogenic transformations both in terms of surface [19] and linear changes [20,21].…”
Section: Introductionmentioning
confidence: 99%